Toads and Tessellations : A Math Adventure - Sharon Morrisette (Watertown, United States Charlesbridge Publishing,U.S., 2012)
Enzo is the son of a great magician, however unlike his father, his spells create chaos instead of order. What really interests Enzo, more than books about magic, are books by and about the lives of famous physicists and astronomers like Galileo Galilei and Johannes Kepler. Enzo dreams not of becoming a magician, but a mathematician instead. When Tessel, the village shoemaker, is called upon to make twelve identical shoes out of only one piece of leather, Aida, the shoemaker's sister, goes to Enzo's father for some magic to help her brother. With Enzo's father out of town at a magic convention, it's up to Enzo to help Aida and Tessel out of their predicament. A spell snafu leads Enzo and Aida to a method of forming patterns without gaps or overlaps, and they discover that math, not magic, may be the answer to their problem. Sharon Morisette's accessible text introduces readers to the concept of tessellations, while Philomena O'Neill's illustrations offer a clear visual to what tiling is--children will enjoy finding the tessellations hidden throughout the images. Back matter includes a glossary and notes about tessellations, Galileo, and Kepler.